Language and Social Justice in US Climate Movements: Barriers and Ways Forward - Fine, Julia Coombs (Frontiers in Communication, 2022)
Climate movements increasingly conceptualize the climate crisis as an issue of social injustice, both in terms of its root causes and its present and future effects. Climate justice calls for participatory decision-making within climate movements, which, as communication scholars have pointed out, necessitates inclusive and accessible communicative practices. Within sociocultural linguistics, a growing body of research has explored sociolinguistic justice, or marginalized groups’ struggle for self-determined language use. This analysis interweaves these two research areas, applying the theory of sociolinguistic justice to climate communication in organizing contexts. Drawing on 67 semi-structured interviews and 112 online surveys with climate activists from organizations across the United States, the analysis finds that sociolinguistic injustice impedes frontline community members’ participation in climate movements. Specific barriers include: (1) English-only communications; (2) the combination of incomprehensible jargon with a dry, emotionless register; (3) the use of Dominant American English in prescriptive climate communication materials such as phonebanking scripts; (4) language policing of discourses of environmental justice and environmental racism; and (5) a form of linguistic ventriloquism in which adult organizers pressure youth to express climate grief in their stead. Climate activists’ insights are synthesized to propose countermeasures to each of these problems of sociolinguistic injustice. The results suggest that sociolinguistic justice can be a useful lens for understanding climate justice communication within climate movements, and provide guidance to climate organizers and educators who wish to align their communications with the inclusive, anti-racist, and decolonial values of climate justice.